2014
DOI: 10.1002/bmc.3273
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive LC‐MS/MS method for simultaneous quantification of eleven constituents in rat serum and its application to a pharmacokinetic study of a Chinese medicine Shengmai injection

Abstract: A sensitive LC-MS/MS method was developed and validated for simultaneous quantification of 11 constituents, ginsenoside Rg1, Re, Rf, Rg2, Rb1, Rd, Rc, ophiopogonin D, schisandrin, schisandrol B and schizandrin B, in rat serum using digoxin as the internal standard (IS). The serum samples were pretreated and extracted with a two-step liquid-liquid extraction. Chromatographic separation was achieved on a C18 analytical column with a proper gradient elution using 0.02% acetic acid aqueous solution and 0.02% aceti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Wang et al performed a simultaneous quantification of multiple components through both positive‐ and negative‐ion electrospray ionization using one IS. Indeed, their validation results indicate that the analysis could be performed reliably with one IS (Ezzeldin, Abo‐Talib, Tammam, & Shahat, ; Wang et al, ; Zhan, Shao, Fan, & Li, ), which is in accordance with our findings.…”
Section: Resultssupporting
confidence: 92%
“…Wang et al performed a simultaneous quantification of multiple components through both positive‐ and negative‐ion electrospray ionization using one IS. Indeed, their validation results indicate that the analysis could be performed reliably with one IS (Ezzeldin, Abo‐Talib, Tammam, & Shahat, ; Wang et al, ; Zhan, Shao, Fan, & Li, ), which is in accordance with our findings.…”
Section: Resultssupporting
confidence: 92%
“…Previous reports showed that time to reach peak concentration ( T max ) is 1 h for BHCl (Liu et al ., ), 0.5 h for emodin and FA (Gong et al ., ; Wen et al ., ), 0.25 h for THSG (Zhao et al ., ), 0.6 h for ginsenoside Rg1 and 1.5 h for ginsenoside Rb1 (Xu et al ., ). The pharmacokinetics of Re and Rg1 are similar because they both belong to the 20 ( S )‐protopanaxatriol type according to their structures (Li et al ., ; Zhan et al ., ). Hence, blood samples of 8 mL were taken from the abdominal aorta 2 h after oral administration and kept standing for 30 min to obtain plasma.…”
Section: Methodsmentioning
confidence: 97%
“…Also, an LLOQ of 1 ng/mL for the three lignans that was reported was at least 20‐times higher than the presently determined limit. The other methods were less sensitive, with LLOQs ranging from 0.23–1.2 ng/mL for schizandrin and 0.26–1.48 ng/mL for gomisin N . In comparison, our approach was more sensitive for three lignans in plasma (LLOQ of 0.05 ng/mL for all three lignans using the LLE method with the small amount of 0.1 mL plasma).…”
Section: Resultsmentioning
confidence: 81%
“…Analytical techniques that have been used to analyze the three lignans include LC–MS , LC–MS/MS , UHPLC–MS/MS , and GC–MS . Among these studies, only two publications suggested an analytical method capable of simultaneously analyzing the three lignans .…”
Section: Introductionmentioning
confidence: 99%